,This question can be solved using a principle called
![\begin{gathered} \text{BODMAS} \\ B=\text{BRACKET} \\ O=OF(*) \\ D=\text{DIVISION(}(\square)/(\square)) \\ M=\text{MULTIPLICATION}(* \\ A=\text{ADDITION}(+ \\ S=\text{SUBTRACTION}(- \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/t2f5jxre5v8ewnrte9tmuv1ik4baw6jsah.png)
The expression given in the question is
![8*6+((12-4)/(2))](https://img.qammunity.org/2023/formulas/mathematics/college/8s06n6928gzotcpo2jxd5fh3vhjqt12juw.png)
From the above principle, we will solve the bracket first, followed by the division sign the followed by the multiplication sign and then finally the addition sign
![\begin{gathered} 8*6+((12-4))/(2) \\ =8*6+(8)/(2)(\text{bracket) (12-4=8)} \\ =8*6+4(\text{division) (8/2 =4)} \\ =48+4(multiplication\text{) (8}*6=48) \\ =52(\text{addition)}(48+4=52) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i5jb1rxx6rcj2l8fjvj3x1aiqzh3z29qgy.png)
Therefore,
The final answer to the above expression is = 52
The correct answer is OPTION A